Trends of the criminal-legal complex in relation to the legislative consolidation of the misdemeanor catego (2022)
The study aims to consider scientific opinions on the feasibility and effectiveness of introducing the misdemeanor category into the Russian criminal-legal complex and conduct a comparative legal analysis within the framework of foreign legislation and a historical retrospective. The authors use the comparative-legal, historical-legal, and statistical methods, as well as the method of systemic analysis. The article studies the issues relevant to criminal and criminal procedure law and related to the legislative consolidation of misdemeanors. Over the past few decades, the main vector of developing and improving modern criminal justice policy has been a course towards the liberalization of criminal liability, which includes discussions on the further decriminalization of certain types of crimes and mitigation of criminal sanctions for some unlawful acts. A key task of modern criminal law is the urgent problem associated with the possibility of reintroducing the misdemeanor category into Russian criminal legislation. The division of criminal acts into misdemeanors and crimes fully corresponds to objective conditions and modern needs. There are several approaches to consolidating the misdemeanor category into Russian criminal legislation. The first approach is to adopt a new Code of Misdemeanor Offenses and the second approach is to include the relevant section into the existing Criminal Code of the Russian Federation.